Regional demands for policy participation in the EU multilevel system - Philipp Studinger; Michael W. Bauer (European Journal of Government and Economics (EJGE), 2012)
Over the past 50 years, an increasing amount of political authority has been delegated to the regional government level in Europe. This paper analyses regional demands for involvement in policy-making by focusing on the preferences of top-level regional civil servants ("regio-crats"). A survey (n=347) of regio-crats in 60 regions of 5 European Union member states serves as the empirical basis for the analysis of regional demands for policy involvement in the multilevel system. The data reveal differential patterns of demands. By and large, regio-crats emerge as being conservative, incremental and modest in their wishes for greater policy involvement, except where the regional contexts are characterised by substantial emancipatory political ambitions or cultural distinctiveness. Regional demands for policy participation in the multilevel system are pragmatic, patch-worked and incremental, and more conservative than transformative.
Keywords: 330; subnational bureaucrats; European Union; policy allocation; multilevel system